2020
DOI: 10.1089/dia.2019.0437
|View full text |Cite
|
Sign up to set email alerts
|

Young Children with Type 1 Diabetes: Sleep, Health-Related Quality of Life, and Continuous Glucose Monitor Use

Abstract: While children with type 1 diabetes (T1D) and their parents report significant sleep problems, few studies have focused on young children and included health-related quality of life (HRQOL) as an outcome of sleep disturbance. In addition, relatively little is known about the use of diabetes devices, such as continuous glucose monitors (CGMs), in young children and their link with sleep disturbances. This brief report examines the relationship between sleep quality and HRQOL and explores sleep disturbances rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
1
25
0
1
Order By: Relevance
“…In a RCT, adolescents' sleep quality measured with the PSQI questionnaire was not different in youth using rtCGM ( 60 ). On the contrary, parental sleep quality improved with the use of rtCGM, both when measured with the PSQI questionnaire as well by accelerometry devices in parents of adolescents and of young children, respectively ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a RCT, adolescents' sleep quality measured with the PSQI questionnaire was not different in youth using rtCGM ( 60 ). On the contrary, parental sleep quality improved with the use of rtCGM, both when measured with the PSQI questionnaire as well by accelerometry devices in parents of adolescents and of young children, respectively ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies the perceived QoL assessed by the PedsQL in patients and caregivers, resulted improved by the use of rtCGM ( 55 , 62 ). In some other studies no variations in the PedsQL were reported ( 13 , 14 ), probably due to the number of variables that may influence the perceived QoL in diabetes or due to the short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent integrative review of 17 original studies on sleep and T1DM reported that young adults with T1DM have large variations in sleep duration, poor quality of sleep, and sleep deficiency [20]. An improvement in sleep quality has been observed in young children (2-5 years) using continuous glucose monitoring; however, continuous glucose monitoring negatively impacted parents' sleep [21]. However, the impact of newer diabetic technologies on sleep quality in young adults with T1DM has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%